Halogen-free low-smoke polyolefin insulated cable and preparation method thereof

By using composite fiber braided layer and porous ceramic protective layer in the cable, the problems of long combustion time and smoke generation are solved, and efficient flame retardant and smoke suppression are achieved, improving the safety performance of the cable.

CN119170335APending Publication Date: 2024-12-20ZHONGDONG CABLE MFR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410969430.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing cables burn for too long when a fire occurs, producing a large amount of smoke and toxic gases, the flame retardant release efficiency is low, making it difficult to quickly retardant in the early stages of the fire, and the polyolefin resin has poor heat resistance.

Method used

The protective layer combined with composite fiber braided layer and porous ceramics is used to delay combustion through heat-resistant inorganic fibers and aramid fiber braided layer. The flame retardant cooperates with porous ceramics to inhibit the formation of carbon particles and the diffusion of smoke. The silicon-aluminum sol is embedded in the pores of ceramic particles. Adsorb smoke particles and toxic substances.

Benefits of technology

It effectively improves the refractory and flame retardant performance of the cable, reduces the smoke density during combustion, realizes the dual role of flame retardant and smoke suppression, and improves the mechanical strength and safety performance of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004952712180000111
    Figure BDA0004952712180000111
  • Figure BDA0004952712180000112
    Figure BDA0004952712180000112
Patent Text Reader

Abstract

The invention relates to a halogen-free low-smoke polyolefin insulated cable and a preparation method thereof. The halogen-free low-smoke polyolefin insulated cable comprises an inner core, a protective layer wrapping the inner core and a braided layer wrapping the protective layer. The woven layer is formed by weaving composite fibers; the composite fibers comprise heat-resistant inorganic fibers and aramid fibers; the protective layer is prepared from the following raw materials: polyethylene resin, a flame retardant, porous ceramic, a compatilizer and an antioxidant; the porous ceramic is prepared by the following method: crushing a porous ceramic preform to obtain ceramic particles; mixing the ceramic particles and the silicon-aluminum sol, heating and stirring to obtain pretreated ceramic particles; and drying the pretreated ceramic particles, and calcining to obtain the porous ceramic. Through the structural design of the inner core, the protective layer and the braided layer, the fireproof and flame-retardant performance of the cable can be effectively improved, the smoke density during combustion is effectively reduced, and the dual effects of flame retardance and smoke suppression are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cable materials, and more specifically, to a halogen-free low-smoke polyolefin insulated cable and a preparation method thereof. Background Art

[0002] Cables are conductors composed of multiple wires, used for the transmission of electrical energy or signals, and are widely used in power, communications, sensors and other fields. Different cable application sites have different performance requirements for cables. Generally speaking, cables need to have good mechanical properties, aging resistance, corrosion resistance, etc. For crowded places, in addition to the above performance requirements, cables also need to have good flame retardant properties.

[0003] At present, flame retardants are generally added to cable protective materials to achieve the purpose of flame retardancy; flame retardants generally include inorganic flame retardants such as aluminum hydroxide and organic flame retardants such as bromine and nitrogen. Compared with organic flame retardants, inorganic flame retardants have the advantages of low toxicity, good thermal stability and low smoke emission, and are environmentally friendly flame retardants. Among them, aluminum hydroxide, as a commonly used flame retardant, mainly reduces the temperature of the burning polymer and reduces the burning rate through endothermic decomposition, and can release water vapor during pyrolysis to dilute the concentration of combustible gas and oxygen, thereby achieving the purpose of flame retardancy. However, since the pyrolysis of aluminum hydroxide takes a certain amount of time, it has the disadvantage of low release efficiency, and it is difficult to quickly retardant the fire at the beginning of the fire, resulting in a long burning time of the cable. In addition, since the sheath material of the cable is mostly based on polyolefin resin as the base material and various performance additives are added, when the cable catches fire, the polyolefin resin with poor heat resistance will still produce a large amount of smoke, toxic gases and other substances when burning, affecting the environment and people's health. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a halogen-free low-smoke polyolefin insulated cable and a preparation method thereof.

[0005] In the first aspect, the present application provides a halogen-free low-smoke polyolefin insulated cable, which adopts the following technical solution:

[0006] A halogen-free low-smoke polyolefin insulated cable, comprising an inner core, a protective layer coated on the inner core, and a braided layer coated on the protective layer;

[0007] The braided layer is braided from composite fibers;

[0008] The composite fiber includes heat-resistant inorganic fiber and aramid fiber;

[0009] The protective layer comprises the following raw materials in parts by weight: 100-120 parts of polyethylene resin, 20-30 parts of flame retardant, 10-20 parts of porous ceramic, 1-5 parts of compatibilizer and 0.1-1 parts of antioxidant;

[0010] The porous ceramic is prepared by the following method:

[0011] crushing the porous ceramic preform to obtain ceramic particles;

[0012] The ceramic particles and the silica-alumina sol are mixed in a weight ratio of 1:(1-3), and heated and stirred to obtain pretreated ceramic particles;

[0013] The pretreated ceramic particles are dried and then calcined to obtain the porous ceramic.

[0014] In some embodiments of the present application, the silica-alumina sol is composed of silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of (1-3):(1-3):5.

[0015] In some embodiments of the present application, the particle size of the ceramic particles is 50-60 mesh;

[0016] The heating and stirring temperature of the ceramic particles and the silica-alumina sol is 60-70° C., and the stirring time is 10-20 hours;

[0017] The drying temperature is 100-110°C and the drying time is 8-10h;

[0018] The calcination temperature is 400-500° C., the calcination time is 3-5 hours, and the calcination atmosphere is nitrogen.

[0019] In some embodiments of the present application, the porous ceramic preform is prepared by the following method:

[0020] The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:(1-3):(2-4), and stirred evenly to obtain a premix;

[0021] After the premix is ​​pressed into shape, a prefabricated embryo body is obtained;

[0022] The prefabricated body is heated at a temperature of 300-400° C. for 2-4 hours; then the temperature is raised to 1000-1100° C. and sintered for 1-2 hours to obtain a porous ceramic prefabricated body.

[0023] In some embodiments of the present application, the ore powder is obtained by mixing diatomaceous earth, alumina powder and calcium feldspar powder in a weight ratio of 1:(1-3):(1-3), and calcining at a temperature of 800-900° C. for 2-3 hours.

[0024] In some embodiments of the present application, the pore-forming agent includes a combination of one or more of starch and wood fiber;

[0025] The bonding solution is composed of a bonding agent and water in a weight ratio of (1-10):100;

[0026] The binder includes a combination of one or more of polyvinyl alcohol, phenolic resin, polyvinyl butyral, polymethyl methacrylate, and epoxy resin.

[0027] In some embodiments of the present application, the heat-resistant inorganic fiber includes a combination of one or more of glass fiber, aluminum silicate fiber, basalt fiber, and carbon fiber.

[0028] In some embodiments of the present application, the mesh size of the woven layer is 800-1000 meshes.

[0029] In some embodiments of the present application, the flame retardant is composed of aluminum oxide trihydrate, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 1:(1-3):(10-15);

[0030] The compatibilizer includes a combination of one or more of a silane coupling agent, a titanate coupling agent, and stearic acid;

[0031] The antioxidant comprises a combination of one or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tris[2,4-di-tert-butylphenyl]phosphite and distearyl thiodipropionate.

[0032] According to a second aspect of the present application, a method for preparing a halogen-free flame-retardant insulated cable is provided, comprising the following steps:

[0033] Covering the inner core with the protective layer to form a first intermediate;

[0034] Covering the braided layer on the first intermediate body to form a second intermediate body;

[0035] The second intermediate is hot-pressed to form the halogen-free and low-smoke polyolefin insulated cable.

[0036] The present application has the following beneficial effects: the present application can effectively improve the fire resistance and flame retardancy of the cable and effectively reduce the smoke density during combustion through the structural design of the inner core, the protective layer and the braided layer; wherein the braided layer woven from composite fibers composed of heat-resistant inorganic fibers and aramid fibers has excellent high temperature resistance. In the early stage of a fire, the braided layer can prevent the protective layer from directly contacting the flame to delay the burning of the cable; in the later stage of a fire, the protective layer can inhibit the formation of carbon particles during polymer degradation through the combination of flame retardants and porous ceramics, and absorb excess smoke particles and toxic substances to achieve the dual effects of flame retardancy and smoke suppression. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0038] In an exemplary embodiment, the present application provides a halogen-free low-smoke polyolefin insulated cable, comprising an inner core, a protective layer coated on the inner core, and a braided layer coated on the protective layer;

[0039] The braided layer is woven from composite fibers;

[0040] The composite fibers include heat-resistant inorganic fibers and aramid fibers;

[0041] The protective layer comprises the following raw materials in parts by weight: 100-120 parts of polyethylene resin, 10-20 parts of porous ceramics, 8-20 parts of flame retardant, 0.5-2 parts of compatibilizer and 0.1-1 parts of antioxidant;

[0042] The porous ceramics are prepared by the following method:

[0043] crushing the porous ceramic preform to obtain ceramic particles;

[0044] The ceramic particles and the silica-alumina sol are mixed in a weight ratio of 1:(1-3), and heated and stirred to obtain pretreated ceramic particles;

[0045] The pretreated ceramic particles are dried and then calcined to obtain porous ceramics.

[0046] In this embodiment, the inner core includes a conductor that can be used for the transmission of electrical energy; the inner core is coated with a protective layer, which has the effect of flame retardancy and reducing the smoke density when the polymer burns; the braided layer coated on the outer surface of the protective layer can play a role in heat resistance and heat insulation. Among them, the braided layer woven from composite fibers composed of heat-resistant inorganic fibers and aramid fibers has excellent high temperature resistance. In the early stage of a fire, the braided layer can prevent the protective layer from directly contacting the flame to delay the combustion of the cable and provide a certain amount of reserved time for the release of the flame retardant; in the later stage of a fire, the protective layer can inhibit the formation of carbon particles when the polymer degrades through the combination of flame retardants and porous ceramics, and absorb excess smoke particles and toxic substances to play a dual role of flame retardancy and smoke suppression.

[0047] When the flame retardant absorbs heat and acts as a flame retardant, it can be combined with the porous ceramic, so that the carbon particles of the polymer degradation form coke and adhere to the porous ceramic with multiple pores. The porous ceramic of this embodiment can embed silicon-aluminum adsorption particles in the pores of the ceramic particles through the treatment of silicon-aluminum sol, which can more efficiently adsorb smoke particles and toxic substances to play a role in inhibiting the spread of smoke.

[0048] In one embodiment, the protective layer includes the following raw materials in parts by weight: 100 parts of polyethylene resin, 10 parts of porous ceramics, 8 parts of flame retardant, 0.5 parts of compatibilizer and 0.1 parts of antioxidant.

[0049] In this embodiment, under the condition of achieving the same flame retardant effect, the amount of flame retardant can be reduced to improve the compatibility between the raw materials of the protective layer, thereby improving the mechanical strength of the cable.

[0050] In one embodiment, the protective layer includes the following raw materials in parts by weight: 120 parts of polyethylene resin, 20 parts of porous ceramics, 20 parts of flame retardant, 2 parts of compatibilizer and 1 part of antioxidant.

[0051] In this embodiment, in order to obtain a better flame retardant effect, the amount of the flame retardant in the protective layer may be increased. At the same time, the compatibility between the raw materials in the raw materials may be improved by increasing the amount of the compatibilizer.

[0052] Exemplarily, the weight ratio of the ceramic particles to the silica-alumina sol is 1:1, 1:2 or 1:3.

[0053] In an exemplary embodiment, the silica-alumina sol is composed of silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of (1-3):(1-3):5.

[0054] In this embodiment, the silica-alumina sol composed of silica sol and sodium tetrahydroxyaluminate can embed silica-alumina adsorption particles in the pores of ceramic particles, which can more efficiently adsorb smoke particles and toxic substances to play a role in inhibiting the spread of smoke.

[0055] Illustratively, the weight ratio of silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in the silica-alumina sol is 1:1:5, 2:2:5 or 3:3:5.

[0056] In an exemplary embodiment, the particle size of the ceramic particles is 50-60 mesh;

[0057] The temperature for heating and stirring the ceramic particles and the silica-alumina sol is 60-70°C, and the stirring time is 10-20h;

[0058] The drying temperature is 100-110°C and the drying time is 8-10h;

[0059] The calcination temperature is 400-500°C, the calcination time is 3-5h, and the calcination atmosphere is nitrogen.

[0060] In one embodiment, the particle size of the ceramic particles is 50 mesh;

[0061] The heating and stirring temperature of the ceramic particles and the silica-alumina sol is 60°C, and the stirring time is 10 hours;

[0062] The drying temperature is 100°C and the drying time is 8h;

[0063] The calcination temperature was 400°C, the calcination time was 3 h, and the calcination atmosphere was nitrogen.

[0064] In one embodiment, the particle size of the ceramic particles is 55 mesh;

[0065] The heating and stirring temperature of the ceramic particles and the silica-alumina sol was 65°C, and the stirring time was 15 h;

[0066] The drying temperature is 105°C and the drying time is 9h;

[0067] The calcination temperature is 450°C, the calcination time is 4h, and the calcination atmosphere is nitrogen.

[0068] In one embodiment, the particle size of the ceramic particles is 60 mesh;

[0069] The heating and stirring temperature of the ceramic particles and the silica-alumina sol is 70°C, and the stirring time is 20 hours;

[0070] The drying temperature is 110°C and the drying time is 10h;

[0071] The calcination temperature was 500°C, the calcination time was 5 h, and the calcination atmosphere was nitrogen.

[0072] In an exemplary embodiment, the porous ceramic preform is prepared by the following method:

[0073] The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:(1-3):(2-4), and stirred evenly to obtain a premix;

[0074] After the premix is ​​pressed into shape, a prefabricated embryo body is obtained;

[0075] The prefabricated body is heated at a temperature of 300-400° C. for 2-4 hours; then the temperature is raised to 1000-1100° C. and sintered for 1-2 hours to obtain a porous ceramic prefabricated body.

[0076] In this embodiment, a porous ceramic preform with high porosity and high adsorption effect can be prepared by the above method.

[0077] In one embodiment, the porous ceramic preform is prepared by the following method:

[0078] The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:1:2, and stirred evenly to obtain a premix;

[0079] After the premix is ​​pressed into shape, a prefabricated embryo body is obtained;

[0080] The prefabricated body was heated at 300° C. for 2 h; then the temperature was raised to 1000° C. and sintered for 1 h to obtain a porous ceramic prefabricated body.

[0081] In one embodiment, the porous ceramic preform is prepared by the following method:

[0082] The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:2:3, and stirred evenly to obtain a premix;

[0083] After the premix is ​​pressed into shape, a prefabricated embryo body is obtained;

[0084] The preformed body was heated at 350° C. for 3 h; then the temperature was raised to 1050° C. and sintered for 1.5 h to obtain a porous ceramic preform.

[0085] In one embodiment, the porous ceramic preform is prepared by the following method:

[0086] The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:3:4, and stirred evenly to obtain a premix;

[0087] After the premix is ​​pressed into shape, a prefabricated embryo body is obtained;

[0088] The preformed body was heated at 400° C. for 4 hours; then the temperature was raised to 1100° C. and sintered for 2 hours to obtain a porous ceramic preform.

[0089] In an exemplary embodiment, the ore powder is obtained by mixing diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:(1-3):(1-3), and calcining at a temperature of 800-900° C. for 2-3 hours.

[0090] The main component of natural diatomaceous earth is SiO 2 , with a special porous structure and good adsorption capacity. The porous ceramic is prepared by using mineral powder composed of diatomite, alumina powder and calcium feldspar in a weight ratio of 1: (1-3) 1: (1-3), which has excellent smoke adsorption capacity.

[0091] In one embodiment, the ore powder is obtained by mixing diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:1:1 and calcining at 800° C. for 2 hours.

[0092] In one embodiment, the ore powder is obtained by mixing diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:2:2 and calcining at 850° C. for 2.5 hours.

[0093] In one embodiment, the ore powder is obtained by mixing diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:3:3 and calcining at 900° C. for 3 hours.

[0094] In an exemplary embodiment, the pore former includes a combination of one or more of starch, wood fiber;

[0095] The bonding solution is composed of a bonding agent and water in a weight ratio of (1-10):100;

[0096] The binder includes a combination of one or more of polyvinyl alcohol, phenolic resin, polyvinyl butyral, polymethyl methacrylate, and epoxy resin.

[0097] Exemplarily, the pore former is starch, or wood fiber, or consists of starch and wood fiber in a weight ratio of 1:1.

[0098] Illustratively, the weight ratio of the binder to water in the binding solution is 1:100, 5:100 or 10:100.

[0099] Exemplarily, the binder is polyvinyl alcohol, or phenolic resin, or consists of polyvinyl butyral and epoxy resin in a weight ratio of 1:1.

[0100] In an exemplary embodiment, the heat-resistant inorganic fiber includes a combination of one or more of glass fiber, aluminum silicate fiber, basalt fiber, and carbon fiber.

[0101] Glass fiber, aluminum silicate fiber, basalt fiber and carbon fiber have many excellent properties such as electrical insulation, corrosion resistance and high temperature resistance. When used as the braiding layer material of the cable, they can play a good role in heat resistance and insulation.

[0102] Exemplarily, the heat-resistant inorganic fiber is glass fiber, aluminum silicate fiber, or basalt fiber, or carbon fiber, or consists of aluminum silicate fiber, basalt fiber and carbon fiber.

[0103] In an exemplary embodiment, the mesh size of the braided layer is 800-1000 mesh.

[0104] In this embodiment, by limiting the size of the mesh of the braided layer, the cable can maintain good heat resistance.

[0105] Exemplarily, the mesh size of the braided layer is 800 mesh, 900 mesh or 1000 mesh.

[0106] In an exemplary embodiment, the flame retardant is composed of aluminum oxide trihydrate, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 1:(1-3):(10-15);

[0107] The compatibilizer includes a combination of one or more of a silane coupling agent, a titanate coupling agent, and stearic acid;

[0108] The antioxidant includes a combination of one or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tris[2,4-di-tert-butylphenyl]phosphite, and distearyl thiodipropionate.

[0109] In this embodiment, the flame retardant is a halogen-free flame retardant, which has the advantages of low smoke and environmental protection. Aluminum hydroxide has the advantages of low price and good flame retardant performance, which can improve the flame retardant performance of the cable; however, it has poor heat resistance, so it cooperates with trihydrate aluminum oxide and ammonium polyphosphate with good heat resistance to play the role of flame retardant, oxygen isolation and smoke reduction.

[0110] Illustratively, the weight ratio of alumina trihydrate, ammonium polyphosphate and aluminum hydroxide in the flame retardant is 1:1:10, or 1:2:12 or 1:3:15.

[0111] Illustratively, the compatibilizer is a silane coupling agent, or a titanate coupling agent, or stearic acid, or consists of a silane coupling agent, a titanate coupling agent, and stearic acid in a weight ratio of 1:1:1.

[0112] Exemplarily, the antioxidant is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], or tris[2,4-di-tert-butylphenyl]phosphite, or disteardithiodipropionate, or is composed of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris[2,4-di-tert-butylphenyl]phosphite in a weight ratio of 1:1.

[0113] In an exemplary embodiment, the present application provides a method for preparing a halogen-free flame-retardant insulated cable, comprising the following steps:

[0114] Covering the inner core with a protective layer to form a first intermediate;

[0115] Covering the braided layer on the first intermediate body to form a second intermediate body;

[0116] The second intermediate is hot pressed to form a halogen-free and low-smoke polyolefin insulated cable.

[0117] In this embodiment, the inner core is a conductor, or it can be a conductor wrapped with an insulating layer. The conductor can be a copper wire, which is used as the inner core of the cable after drawing and annealing. Cables usually have single core, two cores, three cores, four cores, and five cores. Different cable preparation methods can be used according to the number of cores. For example, when the cable is a single core, the raw materials of the protective layer are stirred, melted, extruded, and pressed into shape, and then wrapped around the surface of the inner core to form a protective layer; then the braided layer is wrapped around the protective layer; finally, it is subjected to hot pressing treatment to improve the bonding force between the protective layer and the braided layer, thereby obtaining a halogen-free low-smoke polyolefin insulated cable with better mechanical properties.

[0118] When the cable has a multi-core structure such as two-core or three-core, multiple inner cores are twisted first, and glass fiber ropes are filled between the gaps between the multiple inner cores; then the protective layer is wrapped around the outer periphery of the inner core; then the braided layer is wrapped around the protective layer; finally, after hot pressing treatment, a halogen-free and low-smoke polyolefin insulated cable is obtained.

[0119] The hot pressing temperature is 200-220° C. For example, the hot pressing temperature is 200° C., 210° C., or 220° C.

[0120] In order to more clearly explain the technical solution of the present application, the present application lists specific embodiments of halogen-free low-smoke polyolefin insulated cables, and the beneficial effects of selecting the above-mentioned ranges of the content of each component will be explained by giving specific experimental data through specific embodiments.

[0121] It should be noted that, unless otherwise specified, the raw materials in the following examples can be obtained from commercial sources.

[0122] The polyethylene resin is HDPE, the grade is 5000S, and the density is 0.954g / cm 3 , the melt index (190℃ / 2.16kg) is 0.95g / 10min; the heat-resistant inorganic fiber is selected from glass fiber, and the single filament is 500dtex; the fineness of the aramid fiber is 400dtex; the braided layer is woven with a composite fiber obtained by twisting glass fiber and aramid fiber as yarn; the mesh of the braided layer is 800 mesh; the bonding solution is composed of a binder and water in a weight ratio of 5:100, wherein the binder is polyvinyl alcohol, model PVA17-88; the compatibilizer is silane coupling agent KH-550; the antioxidant is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0123] Preparation Example

[0124] Preparation Example 1: The porous ceramic is prepared by the following method:

[0125] ① Mix diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:1:1, and calcine at 850° C. for 2 h to obtain ore powder.

[0126] ② Mix the ore powder, pore-forming agent and binding solution in a weight ratio of 10:1:2, stir evenly to obtain a premix; press the premix under a pressing pressure of 10 MPa and a pressing time of 30 min to obtain a prefabricated body; heat the prefabricated body at 350°C for 3h; then raise the temperature to 1000°C and sinter for 2h to obtain a porous ceramic preform.

[0127] ③ Evenly mix silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of 1:1:5 to obtain silica-alumina sol; crush the porous ceramic preform to obtain ceramic particles with a particle size of 50 mesh; mix the ceramic particles and silica-alumina sol in a weight ratio of 1:1, heat and stir at 60°C for 10 hours to obtain pretreated ceramic particles; dry the pretreated ceramic particles at 100°C for 8 hours; and then calcine at 400°C for 3 hours to obtain porous ceramics.

[0128] Preparation Example 2: The porous ceramic is prepared by the following method:

[0129] ① Mix diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:2:2, and calcine at 800°C for 3 hours to obtain ore powder.

[0130] ② Mix the ore powder, pore-forming agent and binding solution in a weight ratio of 10:2:3, stir evenly to obtain a premix; press the premix under a pressing pressure of 10 MPa and a pressing time of 30 min to obtain a prefabricated body; heat the prefabricated body at 300°C for 4h; then raise the temperature to 1050°C and sinter for 1h to obtain a porous ceramic preform.

[0131] ③ Evenly mix silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of 2:2:5 to obtain silica-alumina sol; crush the porous ceramic preform to obtain ceramic particles with a particle size of 50 mesh; mix the ceramic particles and silica-alumina sol in a weight ratio of 1:2, heat and stir at 60°C for 10 hours to obtain pretreated ceramic particles; dry the pretreated ceramic particles at 100°C for 8 hours; and then calcine at 400°C for 3 hours to obtain porous ceramics.

[0132] Preparation Example 3: The porous ceramic is prepared by the following method:

[0133] ① Mix diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:3:3, and calcine at 900° C. for 2 h to obtain ore powder.

[0134] ② Mix the ore powder, pore-forming agent and binding solution in a weight ratio of 10:3:4, stir evenly to obtain a premix; press the premix under a pressing pressure of 10 MPa and a pressing time of 30 min to obtain a prefabricated body; heat the prefabricated body at 400°C for 2h; then raise the temperature to 1100°C and sinter for 1h to obtain a porous ceramic preform.

[0135] ③ Evenly mix silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of 3:3:5 to obtain silica-alumina sol; crush the porous ceramic preform to obtain ceramic particles with a particle size of 50 mesh; mix the ceramic particles and silica-alumina sol in a weight ratio of 1:3, heat and stir at 60°C for 10 hours to obtain pretreated ceramic particles; dry the pretreated ceramic particles at 100°C for 8 hours; and then calcine at 400°C for 3 hours to obtain porous ceramics.

[0136] Preparation Example 4: The difference between this preparation example and preparation example 1 is that the diatomaceous earth and alumina powder in step ① are replaced by an equal amount of calcium feldspar.

[0137] Preparation Example 5: This preparation example differs from Preparation Example 1 in that step ③ is not included. That is, the porous ceramic is prepared by the following method:

[0138] ① Mix diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:1:1, and calcine at 850° C. for 2 h to obtain ore powder.

[0139] ② Mix the ore powder, pore-forming agent and binding solution in a weight ratio of 10:1:2, stir evenly to obtain a premix; press the premix under a pressing pressure of 10 MPa and a pressing time of 30 min to obtain a prefabricated body; heat the prefabricated body at 350°C for 3h; then raise the temperature to 1000°C and sinter for 2h to obtain a porous ceramic.

[0140] Example

[0141] Embodiment 1: A method for preparing a halogen-free low-smoke polyolefin insulated cable, comprising the following steps:

[0142] (1) 100 kg of polyethylene resin, 10 kg of porous ceramics, 8 kg of flame retardant, 0.5 kg of compatibilizer and 0.1 kg of antioxidant were mixed and stirred uniformly, heated to 180° C., melt-extruded, and pressed to obtain a protective layer raw material;

[0143] (2) Drawing and annealing the copper wire to obtain a conductor;

[0144] (3) wrapping the protective layer around the outer periphery of the inner core to obtain a first intermediate;

[0145] (4) coating the first intermediate with the braided layer to obtain a second intermediate;

[0146] (5) The second intermediate is hot-pressed at 200° C. for 20 minutes to obtain a halogen-free and low-smoke polyolefin insulated cable.

[0147] Among them, the thickness of the protective layer is 2mm, and the thickness of the braided layer is 0.2mm.

[0148] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 2-4 of the preparation method of the halogen-free low-smoke polyolefin insulated cable, wherein the formulas of Examples 2-4 are shown in Table 1.

[0149] It should be noted that, except for the data in Table 1, the raw material dosage and process parameters in Examples 2-4 are basically the same as those in Example 1.

[0150] Table 1 Table of the amount of raw materials used for the protective layer of Examples 1-4 (unit: kg)

[0151]

[0152] Comparative Example

[0153] Comparative Example 1: This comparative example is different from Example 1 in that no braided layer is provided outside the protective layer.

[0154] Comparative Example 2: The difference between this comparative example and Example 1 is that the porous ceramic in the protective layer is prepared using Preparation Example 5.

[0155] Performance Testing

[0156] Smoke density: According to GB / T8323.2-2008 "Plastic Smoke Generation Part 2: Single Chamber Test Method for Determination of Smoke Density", the smoke density of the cable when burning is tested.

[0157] Flame retardant performance: Cut the cables into 15 cm lengths one by one, and then place them vertically and burn them with a blowtorch with a heat power of 500W for 15 seconds with a flame height of 125mm, then stop for 15 seconds. Repeat the burning five times and record the flame burning time.

[0158] Vertical combustion: According to UL94-2006 "Test Standard for Flammability of Plastic Combustion Materials in Equipment and Installations", the vertical combustion performance of the cable is evaluated, and the flame retardant performance is ranked from good to bad as V-0, V-1, and V-2.

[0159] The performance test results are shown in Table 2.

[0160] Table 2 Performance test table of the cables of the embodiment and the comparative example

[0161]

[0162] According to the data in Table 2 and in combination with Examples 1-4, it can be seen that the cable prepared by the method of the embodiment of the present application has excellent flame retardant properties, and has a low smoke density when the cable burns, which can effectively suppress the diffusion of smoke, indicating that the cable of the present application has the dual effects of flame retardancy and smoke suppression.

[0163] According to the data in Table 2 and in combination with Example 1 and Comparative Example 1, it can be seen that the flame retardant performance of the cable can be significantly improved by arranging a braided layer outside the protective layer. In combination with Example 1 and Comparative Example 2, it can be seen that when preparing porous ceramics, the silica-alumina sol composed of silica sol and sodium tetrahydroxyaluminate can embed silica-alumina adsorption particles in the pores of ceramic particles, which can more efficiently adsorb smoke particles and toxic substances, so as to play a more efficient role in inhibiting the spread of smoke.

[0164] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A halogen-free low-smoke polyolefin insulated cable, It is characterized in that It comprises an inner core, a protective layer covering the inner core, and a braided layer covering the protective layer; The braided layer is braided from composite fibers; The composite fiber includes heat-resistant inorganic fiber and aramid fiber; The protective layer comprises the following raw materials in parts by weight: 100-120 parts of polyethylene resin, 10-20 parts of porous ceramics, 8-20 parts of flame retardant, 0.5-2 parts of compatibilizer and 0.1-1 parts of antioxidant; The porous ceramic is prepared by the following method: crushing the porous ceramic preform to obtain ceramic particles; The ceramic particles and the silica-alumina sol are mixed in a weight ratio of 1:(1-3), and heated and stirred to obtain pretreated ceramic particles; The pretreated ceramic particles are dried and then calcined to obtain the porous ceramic.

2. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The silica-alumina sol is composed of silica sol, sodium tetrahydroxyaluminate and anhydrous ethanol in a weight ratio of (1-3):(1-3):

5.

3. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The particle size of the ceramic particles is 50-60 mesh; The heating and stirring temperature of the ceramic particles and the silica-alumina sol is 60-70° C., and the stirring time is 10-20 hours; The drying temperature is 100-110°C and the drying time is 8-10h; The calcination temperature is 400-500° C., the calcination time is 3-5 hours, and the calcination atmosphere is nitrogen.

4. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The porous ceramic preform is prepared by the following method: The ore powder, the pore former and the binding solution are mixed in a weight ratio of 10:(1-3):(2-4), and stirred evenly to obtain a premix; After the premix is ​​pressed into shape, a prefabricated embryo body is obtained; The prefabricated body is heated at a temperature of 300-400° C. for 2-4 hours; then the temperature is raised to 1000-1100° C. and sintered for 1-2 hours to obtain a porous ceramic prefabricated body.

5. The halogen-free low-smoke polyolefin insulated cable according to claim 4, It is characterized in that The ore powder is obtained by mixing diatomite, alumina powder and calcium feldspar powder in a weight ratio of 1:(1-3):(1-3), and calcining at a temperature of 800-900° C. for 2-3 hours.

6. The halogen-free low-smoke polyolefin insulated cable according to claim 4, It is characterized in that The pore-forming agent includes a combination of one or more of starch and wood fiber; The bonding solution is composed of a bonding agent and water in a weight ratio of (1-10):100; The binder includes a combination of one or more of polyvinyl alcohol, phenolic resin, polyvinyl butyral, polymethyl methacrylate, and epoxy resin.

7. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The heat-resistant inorganic fiber includes a combination of one or more of glass fiber, aluminum silicate fiber, basalt fiber and carbon fiber.

8. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The mesh size of the braided layer is 800-1000 meshes.

9. The halogen-free low-smoke polyolefin insulated cable according to claim 1, It is characterized in that The flame retardant is composed of aluminum oxide trihydrate, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 1:(1-3):(10-15); The compatibilizer includes a combination of one or more of a silane coupling agent, a titanate coupling agent, and stearic acid; The antioxidant comprises a combination of one or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tris[2,4-di-tert-butylphenyl]phosphite and distearyl thiodipropionate.

10. A method for preparing the halogen-free low-smoke polyolefin insulated cable according to any one of claims 1 to 9, It is characterized in that The steps include: Covering the inner core with the protective layer to form a first intermediate; Covering the braided layer on the first intermediate body to form a second intermediate body; The second intermediate is hot-pressed to form the halogen-free and low-smoke polyolefin insulated cable.

Citation Information

Cited By

  • Braided insulation composite cable support and preparation method and application thereof

    CN120896061A

  • High-effect composite structure power cable and preparation method thereof

    CN121355005A